The Estimated Impact of Implementing a Funding Allocation Formula on the Number of Gonorrhea Cases in the United States, 2014 to 2018. Issue 9 (11th September 2021) - Aslam, Maria Vyshnya; Chesson, Harrell
Abstract : Using a simple model and state-level data on federal sexually transmitted disease prevention funding, we estimated 5222 gonorrhea cases averted from 2014 to 2018 by reallocating resources toward US jurisdictions with greater disease burden. Supplemental digital content is available in the text. Abstract : Background: The Centers for Disease Control and Prevention (CDC) allocates funds annually to state and local programs in the United States to monitor and prevent sexually transmitted diseases (STDs). In 2014, a funding formula was implemented to allocate prevention funds to jurisdictions according to their STD burden and population size. We estimated the effect of implementing the funding formula in terms of gonorrhea cases averted from 2014 to 2018, a period during which inflation-adjusted CDC STD prevention funding declined. Methods: Our model assumed that STD prevention funds have a measurable effect on subsequent reported gonorrhea case rates, and the magnitude of this effect was as estimated in an empirical analysis of decades of state-level gonorrhea rates. In applying this equation-based model, we assumed all factors affecting jurisdictions' gonorrhea rates were constant over time except for their STD prevention funding allocations. We used data on CDC STD prevention funding allocated to each jurisdiction over time. We estimated gonorrhea rates under the "funding formula" scenario compared with a hypothetical "status quo" funding scenario, which reflected traditional methods to allocate prevention funds. Results: In the model, gonorrhea cases increased from 2014 to 2018 by approximately 6% because of a decline in prevention funding, regardless of how funds were allocated. However, the estimated increase in gonorrhea cases was 5222 (range, 1181–9195) cases less in the funding formula scenario than in the status quo scenario. Conclusions: By shifting resources toward jurisdictions with greater disease burden, the funding formula averted a substantial number of gonorrhea cases at no additional cost.